BRIDGING GENERAL AND ACADEMIC ENGLISH: REFLECTIVE INSIGHTS FROM A TESOL PRACTICUM IN UZBEKISTAN - Nazokat Barnoyeva Zokirjonovna, (PEDAGOGS, 2025)
Abstract: This study reports on a TESOL practicum conducted with B2-level first-year undergraduates at Alfraganus University, Tashkent, Uzbekistan, aimed at bridging the gap between general and academic English. Despite solid general English proficiency, students struggled with academic listening, writing, and speaking. Three scaffolded lessons focusing on authentic academic listening, paragraph coherence with article accuracy, and fluency plus pronunciation in academic discussions were implemented. Data from observations, learner reflections, and peer feedback reveal that scaffolded instruction, authentic materials, and collaborative tasks improved learner confidence and performance. The study highlights the value of reflective practice grounded in communicative and task-based approaches and stresses the importance of equity and identity considerations in multilingual TESOL contexts. Recommendations include context-sensitive and inclusive strategies for supporting academic English development.